2017
DOI: 10.1142/s021827181741022x
|View full text |Cite
|
Sign up to set email alerts
|

Detection principle of gravitational wave detectors

Abstract: With the first two detections in late 2015, astrophysics has officially entered into the new era of gravitational wave observations. Since then, much has been going on in the field with a lot of work focussing on the observations and implications for astrophysics and tests of general relativity in the strong regime. However much less is understood about how gravitational detectors really work at their fundamental level. For decades, the response to incoming signals has been customarily calculated using the ver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Owing to amplitude and frequency modulations induced by the motion of the detector around the Sun (LISA) or Earth (LV and ET), the amplitude of the wave is particularly well measured. As the observed GW strain is inversely proportional to the luminosity distance [20,21], the luminosity distance is determined very accurately.…”
Section: Standard Sirens and Weak Lensingmentioning
confidence: 99%
“…Owing to amplitude and frequency modulations induced by the motion of the detector around the Sun (LISA) or Earth (LV and ET), the amplitude of the wave is particularly well measured. As the observed GW strain is inversely proportional to the luminosity distance [20,21], the luminosity distance is determined very accurately.…”
Section: Standard Sirens and Weak Lensingmentioning
confidence: 99%
“…It has long been acknowledged (see, for instance, Schutz (1986); Krolak & Schutz (1987); Chernoff & Finn (1993); Markovic (1993); Finn (1996); Wang & Turner (1997); Thorne (1997); Zhu et al (2001); Holz & Hughes (2005); Dalal et al (2006); ; Nissanke et al (2013)) that gravitationalwave inspiral detections would provide us with invaluable cosmological information. Since the amplitude of a binary's gravitational-wave signal encodes its luminosity distance (Congedo 2017), binary inspirals became known as standard sirens (Schutz 1986), which are the gravitational-wave analogues of type Ia supernovae standard candle measurements. In particular, the determination of the Hubble constant from gravitational-wave standard sirens (Schutz 1986;Krolak & Schutz 1987;Chernoff & Finn 1993;Finn 1996;Dalal et al 2006;Nissanke et al 2013) was demonstrated for the first time by the nearly concurrent joint observations of the electromagnetic counterpart (see Abbott et al (2017c,d); Goldstein et al (2017); Soares-Santos et al (2017); Coulter et al (2017); Savchenko et al (2017); Valenti et al (2017); Arcavi et al (2017); Tanvir et al (2017), and references therein) to the gravitational-wave signal (Abbott et al 2017a) produced by the merger of the binary neutron star system GW170817 which has been localised to the host galaxy NGC 4993.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been acknowledged (see, for instance, Schutz (1986); Krolak & Schutz (1987); Chernoff & Finn (1993); Markovic (1993); Finn (1996); Wang & Turner (1997); Thorne (1997); Zhu et al (2001); Holz & Hughes (2005); Dalal et al (2006); ; Nissanke et al (2013)) that gravitationalwave inspiral detections would provide us with invaluable cosmological information. Since the amplitude of a binary's gravitational-wave signal encodes its luminosity distance (Congedo 2017), binary inspirals became known as standard sirens (Schutz 1986), which are the gravitational-wave analogues of type Ia supernovae standard candle measurements. In particular, the determination of the Hubble constant from gravitational-wave standard sirens (Schutz 1986;Krolak & are expected to be significantly improved after the detection of additional standard siren events.…”
Section: Introductionmentioning
confidence: 99%